(untitled) (Seminário Internacional de Informação, Tecnologia e Inovação, 2024)
The rise of Digital Repositories has taken research on the longevity of digital inventories to a new level. Currently, Digital Preservation is facing the challenge of delimiting its borders so that it can rise to a level of maturity. The objective of this work is based on the survey of information on the subject of digital preservation management in the national literature in order to identify the relevance of the subject in the scientific production, aiming that the survey would be able to assist in the development of an in-depth study in the scope of of the research project Digital Preservation and Risk Analysis in Institutional Repositories of Rede Cariniana. The applied methodology was the survey of publications and records that mentioned the theme. As a result, it was identified that there is a concise but dense literature that mentions the management of Digital Preservation, but does not present a structure that is considered as a management architecture for Digital Preservation. It is concluded that despite the incipient theme, the information gathered is relevant and serves as a motto for an in-depth study, especially when compared with the international scientific production.